Cultivar and nitrogen fertilization effects on Striga infestation and grain yield of early maturing tropical maize - Kamara, A.; Menkir, A.; Chikoye, David; Omoigui, L.O.; Ekeleme, F. (2007)
Striga hermonthica (Del.) Benth. is a parasitic weed that attacks maize, sorghum, and other staple cereal crops in the West African savannas. It is widely believed that Striga thrives best in areas of low soil fertility. This study was conducted to determine the effects of nitrogen (N) fertilization and maize cultivar on Striga emergence and damage, and the grain yield of early maturing maize. Four Striga-tolerant early maturing maize cultivars and one susceptible check were evaluated at four N levels under artificial infestation with S. hermonthica. The experiment was conducted in Mokwa and Abuja, Nigeria, during the 2004 and 2005 cropping seasons. The number of Striga that emerged per plot, Striga damage on the host plant, days to silking, number of ears per plant, and grain yield were measured. Application of N to maize did not affect Striga infestation but significantly reduced damage to host plants and increased the grain yield at 60 and 120 kg N ha -1. Maize response to N was better under non-infested conditions. Maize cultivars did not significantly differ in grain yield under Striga-free conditions, indicating that the cultivars had a similar yield potential. However, under Striga infestation, ACR 94TZECOMP5-W and ACR 94TZECOMP5-Y recorded higher grain yield than the other cultivars, probably due to a lower number of emerged Striga and lower damage ratings. Reduction in Striga damage with increasing N rate was more pronounced in Striga-tolerant cultivars. Farmers should, therefore, derive more benefit from N application under Striga infestation if they grow Striga-tolerant cultivars. Two maize cultivars, previously selected for tolerance to Striga, recorded higher damage symptoms and a lower grain yield, similar to that of the susceptible check. There is, therefore, a need to confirm the response of these cultivars to Striga before promoting them for production by farmers.